Iodine dose of administered contrast media affects the level of radiation-induced DNA damage during cardiac CT scans - Van Cauteren, T; Honoria Da Silva, E; Van Gompel, G; Kersemans, V; Sermon, K; De Mey, J; Buls, N (American Roentgen Ray Society, 2019)
OBJECTIVE. The purpose of this study is to investigate the contributing effect of contrast media (CM) iodine dose on radiation-induced DNA damage in blood lymphocytes during a cardiac CT scan. MATERIALS AND METHODS. The minipigs were exposed 12 times in total to a fixed cardiac CT scan protocol. An unenhanced and two CM injection protocols were considered, the latter with 50% saline diluted (160 mg I/mL) and standard iodixanol. Blood samples were collected before and after CT, and radiation-induced DNA double-strand breaks were assessed using γ-H2AX (H2A histone family member X) immunofluorescent staining of the blood lymphocytes. Significant differences in foci numbers were investigated with an independent sample t test. In addition, a numeric dosimetry model was applied that simulates the cardiac CT scan, with the heart represented by a blood volume containing a mixture of six iodine concentrations (0, 10, 20, 30, 40, and 50 mg I/mL). RESULTS. Compared with the unenhanced (0 mg I/mL) protocol, the number of γ-H2AX foci per cell increased significantly (p < 0.038), by 56.1% for the reduced iodine dose (160 mg I/mL) and by 141.1% for the standard iodine dose (320 mg I/mL) protocols. These in vivo results are confirmed by the dosimetry simulation model, in which 78.8% and 133.7% increases in locally absorbed blood dose in the left ventricle were observed for the reduced and standard iodine dose protocols, respectively. CONCLUSION. Administration of CM during a cardiac CT examination significantly increases radiation-induced DNA damage in blood lymphocytes. Moreover, a lower CM iodine dose results in a reduced level of DNA damage, at constant radiation exposure.